Peran Guru Pendidikan Agama Islam Dalam Mengatasi Kenakalan Siswa Kelas V SDN 2 Kebulusan, Pejagoan, Kebumen - Hanum, Nila Lela; Khasanah, Nginayatul (IAINU Kebumen, 2026)
The aim of this research is to determine the role of Islamic Religious Education Teachers in dealing with delinquency in class V students at SDN 2 Kebulusan, Pejagoan District, Kebumen Regency. This research uses a qualitative approach by collecting data in the form of interviews, observation and documentation. The data analysis technique is in the form of data reduction, data presentation and drawing conclusions. Based on the research results, the role of Islamic Religious Education. Teachers in dealing with student delinquency in class V is the teacher as educator, teacher as guide, teacher as role model, teacher as advisor and teacher as evaluator. There are 3 types of student delinquency, namely mild delinquency, moderate delinquency and serious delinquency. The factors that influence student delinquency are family factors, social factors, religious factors, school factors and student mental factors